2013
DOI: 10.12968/ijpn.2013.19.12.593
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' experiences caring for patients and families dealing with malignant bowel obstruction

Abstract: Malignant bowel obstruction (MBO) is a well-recognised complication of advanced abdominal and pelvic cancers. Often surgical intervention is not feasible, resulting in complex symptoms and an unpredictable course. Although symptom management is a crucial part of nursing care, psychosocial and emotional issues frequently emerge for patients and families. This qualitative study explored the perspectives of nurses from a palliative care unit, in-patient acute care oncology units, ambulatory cancer setting, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…The nurses' availability made them natural points of contact for the patient and the family, as well as for other health professionals. Hence, the nurses described themselves as coordinators of services, aiming at providing care for the patients and their families (Austin et al., ; Daines et al., ; Hopkinson, Hallett, & Luker, ; Howell et al., ; King et al., ; Raphael et al., ; Törnquist et al., ; Wallerstedt & Andershed, ). Schaepe, Campbell, and Bolmsjo () showed that nurses, whether working in home care or hospital in Uganda, described their role as “spiders in a web.” Their work was characterised by networking with other professionals and between the patient and the family.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The nurses' availability made them natural points of contact for the patient and the family, as well as for other health professionals. Hence, the nurses described themselves as coordinators of services, aiming at providing care for the patients and their families (Austin et al., ; Daines et al., ; Hopkinson, Hallett, & Luker, ; Howell et al., ; King et al., ; Raphael et al., ; Törnquist et al., ; Wallerstedt & Andershed, ). Schaepe, Campbell, and Bolmsjo () showed that nurses, whether working in home care or hospital in Uganda, described their role as “spiders in a web.” Their work was characterised by networking with other professionals and between the patient and the family.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, providing psychosocial and spiritual care to the patients went hand in hand with direct hands-on physical care (Kaasalainen et al, 2014;Schaepe et al, 2011). The study by Daines et al (2013) found that the best part of working with palliative care patients across institutions, in acute care and outpatient care as well as in a palliative care unit, was when nurses were able to find the right combination of medical and nonmedical intervention to achieve comfort. The nurse's role across continents and institutions included helping patients with the "soul pain," referring to the more psycho-existential dimension of suffering (Evans & Hallett, 2007;Howell et al, 2014;Kaasalainen et al, 2014;Zheng, Guo, Dong, & Owens, 2015).…”
Section: Doing What's Neededmentioning
confidence: 99%
See 2 more Smart Citations
“…The goals of treatment include relieving nausea and vomiting, allowing oral intake, and alleviating pain. 13 The optimal procedure is that which is the quickest, safest, and most efficacious in alleviating the obstruction. Persistent obstructions in the face of conservative therapy (usually nasogastric decompression, hydration, and bowel rest) or evidence of complete obstructions are indications that a surgical procedure should be considered.…”
Section: Malignant Bowel Obstructionmentioning
confidence: 99%